Dissenting bodies : corporealities in early New England - Finch, Martha L. (Columbia University Press, 2010)
For the Puritan separatists of seventeenth-century New England, ""godliness, "" as manifested by the body, was the sign of election, and the body, with its material demands and metaphorical significance, became the axis upon which all colonial activity and religious meaning turned. Drawing on literature, documents, and critical studies of embodiment as practiced in the New England colonies, Martha L. Finch launches a fascinating investigation into the scientific, theological, and cultural conceptions of corporeality at a pivotal moment in Anglo-Protestant history. Not only were se.